Pengaruh Kedisiplinan dalam Kelas dengan Hasil Belajar Siswa SMP N 1 Kuantan Mudik - Idris, Nadia; Mukhlis, Muhammad (UIR Press, 2023)
The implementation of this research was motivated by the many shortcomings of student discipline in the classroom that affected the learning outcomes of these students in the classroom. The initial step of this research is the distribution of questionnaires to students related to discipline in the classroom and also the comparison with student learning outcomes. Furthermore, students are asked to answer honestly regarding how their activities during Indonesian language learning take place. The results of this research are expected to improve student discipline. Based on the implementation of this study, it can be concluded that based on the significant value of Sig (2-tailed) between discipline in class and with learning outcomes Indonesian grade VIII students is 0.000 < 0.05 which means there is a significant correlation between discipline in class and with learning outcomes Indonesian grade VIII students. Because r count or pearson correlation in this analysis is positive, it means that there is a positive relationship between discipline in class and with learning outcomes Indonesian grade VIII students. The correlation between classroom discipline (X) and Indonesian learning outcomes (Y) is 61.0%. Based on the correlation value interval, the level of influence of discipline in class (X) with learning outcomes Indonesian (Y) is strong, namely in the range of 0.60 – 0.799. Based on the results of hypothesis calculations through the SPSS program, it turns out that Fhitung>Ftabel, which is 68.556> 3.75 thus means that there is a positive and significant influence on the use of discipline in the classroom with student learning outcomes in the midterm exam in grade VIII SMP Negeri 1 Kuantan Mudik.